Production of bioethanol from food waste: Status and perspectives. (September 2022) - Singh, Anusuiya; Singhania, Reeta Rani; Soam, Shveta; Chen, Chiu-Wen; Haldar, Dibyajyoti; Varjani, Sunita; Chang, Jo-Shu; Dong, Cheng-Di; Patel, Anil Kumar
Graphical abstract: Highlights: Food waste could be a zero-waste raw material for value addition. Food waste bioconversion could resolve its management/disposal issue. Food waste conversion to bioethanol could help in attaining energy security. LCA studies for food waste conversion to ethanol proves its feasibility. Abstract: There is an immediate global requirement for an ingenious strategy for food waste conversion to biofuels in order to replace fossil fuels with renewable resources. Food waste conversion to bioethanol could lead to a sustainable process having the dual advantage of resolving the issue of food waste disposal as well as meeting the energy requirements of the increasing population. Food waste is increasing at the rate of 1.3 billion tonnes per year, considered to be one-third of global food production. According to LCA studies discarding these wastes is detritus to the environment, therefore; it is beneficial to convert the food waste into bioethanol. The CO2 emission in this process offers zero impact on the environment as it is biogenic. Among several pretreatment strategies, hydrothermal pretreatment could be a better approach for pretreating food waste because it solubilizes organic solids, resulting in an increased recovery of fermentable sugars to produce bioenergy.